GENERALIZATION OF PROSPECTIVE TECHNOLOGIES FOR INCREASING HYDROCARBON EXTRACTION FROM NATURAL GAS FIELDS - Matkivskyі S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
The vast majority of hydrocarbon fields in Ukraine are at the final stage of development, characterized by complicated conditions for hydrocarbon production. The difficulty of extracting residual hydrocarbon reserves is associated with low reservoir pressures, high water cut, destruction of the bottomhole formation zone, and corrosion of underground and surface equipment. The depletion of the main fields in terms of production and reserves leads to a decrease in hydrocarbon production levels. The fields discovered in recent years are characterized by a complex structure, large depths of productive reservoirs, insignificant reserves and cannot significantly affect the maintenance of hydrocarbon production. Therefore, the main potential reserve for increasing production levels is the residual reserves of depleted fields. The raw material base of such reservoirsis characterized by a deterioration in the quality and structure of reserves over time and is accompanied by an increase in the share of hard-to-extract reserves. To increase the efficiency of development of proven hydrocarbon reserves, existing approaches have been improved and new approaches have been developed for the extraction of hydrocarbons from watered formations, the extraction of retrograde condensate that fell during the development of gas condensate fields for depletion, and the cleaning of bottomhole zones of gas and gas condensate wells and wells. Negative influence of complicating factors during their operation. However, increasing the efficiency of oil and gas field development is possible by investing in the implementation of developed technologies, which will increase their production capabilities in conditions of a significant shortage of hydrocarbon raw materials in Ukraine. Due to the high technological efficiency of secondary technologies for the development of hydrocarbon fields, which is also confirmed by industrial data, their implementation in the fields of Ukraine is recommended.